2004
DOI: 10.1111/j.0902-0055.2002.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human herpes virus‐8 in saliva and non‐lesional oral mucosa in HIV‐infected and oncologic immunocompromised patients

Abstract: HHV-8 is present in the saliva and the non-lesional oral mucosa (not simultaneously) of patients with impaired immunity, with or without HIV co-infection. The oral epithelium seems to represent an independent location of viral residency and may be of viral replication; the clinical implications need further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
(43 reference statements)
3
17
0
4
Order By: Relevance
“…A 4-to 26-fold-increased odds of HHV shedding in the saliva of HIV seropositive patients was observed. The frequencies of detection in the HIV-positive and HIV-negative groups are consistent with those previously reported, indicating that HHVs are frequently shed asymptomatically in the saliva of HIV-infected patients who take HAART (3,4,6,19,37,38,44,68). The higher prevalence in the HIV-positive group may reflect altered health status or differences in herpesvirus seropositivity between the groups, particularly for CMV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A 4-to 26-fold-increased odds of HHV shedding in the saliva of HIV seropositive patients was observed. The frequencies of detection in the HIV-positive and HIV-negative groups are consistent with those previously reported, indicating that HHVs are frequently shed asymptomatically in the saliva of HIV-infected patients who take HAART (3,4,6,19,37,38,44,68). The higher prevalence in the HIV-positive group may reflect altered health status or differences in herpesvirus seropositivity between the groups, particularly for CMV.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of HHVs in the saliva of human immunodeficiency virus (HIV)-seropositive patients has been less often reported, with reports generally focusing on individual prevalence, not the simultaneous presence of HHVs. In these reports, the prevalence of HHVs appears higher in HIV-seropositive patients (3,4,6,19,38,44,46,68). However, in one study that examined multiple HHVs, rates of detection in saliva of HIV-seropositive patients were similar to that of the general population, except for CMV (20).…”
mentioning
confidence: 94%
“…The present data is consistent with other studies that showed evidence of infection with HHVs in the majority of the world's populations [27][28][29][30] .…”
Section: Ethicalsupporting
confidence: 93%
“…That virus replicates at these sites is suggested by data from patient 2, whose viral load in whole-mouth saliva exceeded 2 million genome copies/ ml and in whom viral DNA could be detected in both buccal and palatal exfoliate samples. For most of the patients studied, whole-mouth saliva yielded higher PCR amplification rates than other oral samples, likely reflecting virus shed from other sites, such as tonsils [Koelle et al, 1997;Chagas et al, 2006] and tongue [Triantos et al, 2004;Widmer et al, 2006]. The limited human herpesvirus 8 DNA detection rate in saliva collected from the parotid duct supports previous findings indicating that major salivary glands are not important contributors to viral shedding [Pauk et al, 2000;Beyari et al, 2003].…”
Section: Discussionsupporting
confidence: 74%
“…The mouth and oropharynx are dominant sites of viral shedding [Di Alberti et al, 1997;Koelle et al, 1997;Blackbourn et al, 1998;Lampinen et al, 2000;Pauk et al, 2000;Cook et al, 2002a;Beyari et al, 2003;Duus et al, 2004;Mbopi-Keou et al, 2004;Mbulaiteye et al, 2004;Taylor et al, 2004;Triantos et al, 2004;Widmer et al, 2006;Casper et al, 2007]. Furthermore, virus in the mouth may belong to distinct strains, reflecting multiple infection [Beyari et al, 2003].…”
Section: Introductionmentioning
confidence: 99%